EVALUASI EFEKTIVITAS RESTORATIVE JUSTICE BAGI PENGGUNA NARKOTIKA: STRATEGI MITIGASI OVERCROWDING DI LAPAS - Fadhilah, Rezky Hadyanti (Truth de Journal, 2025)
Narcotics abuse in Indonesia has triggered a public health crisis and stagnation of the legal system due to repressive judicial patterns that have an impact on overcrowding in correctional institutions and potential human rights violations. This study aims to evaluate the effectiveness of the implementation of the principles of Restorative Justice for narcotics abusers and identify challenges that hinder its application. Using normative juridical methods, this study examines current regulations and policies associated with criminal theory and the criminal justice system. The results of the study show that the Restorative Justice approach can be a strategic solution to create a more humane and just justice system through rehabilitation optimization. This study recommends strategic steps for policymakers to improve the implementation of Restorative Justice to reduce the burden on prisons while effectively rehabilitating narcotics abusers. Through this approach, it is hoped that a more integrative and recovery-oriented transformation of Indonesia's criminal justice system will be created.